Acnistus arborescens (Solanaceae): An important food resource for birds in an Atlantic Forest site, Southeastern Brazil - Azimoff, Izar (2020)
Biotic interactions related to the consumption of floral nectar and fruits as food resource by birds promoting plant pollination and dispersal, are essential for forest ecosystem functioning. The daily interaction of birds with Acnistus arborescens (L.) Schltdl. (Solanaceae), a shrub-tree, was studied in the Itatiaia National Park and its surroundings. Reproductive phenology was monthly monitored in eighteen individuals in 2015. During flowering (August to November) and fruiting (September to December) the interaction birds-plant was studied. Flowers were visited by seven hummingbird species and several insects. Fruit set was 87.3%. Thirty-five bird species of eleven families consumed its fruit. Thraupidae with sixteen bird species was the family responsible for most of its frugivory (53.9%). Considering that more than 10% of the birds richness of Itatiaia National Park INP interacts with A. arborescens, it can be considered an important plant species in maintaining local bird diverstity. Thus, for attracting many birds, A. arborescens can be used in the process of recovery of degraded areas, and also as a focal plant species for environmental education programs and birdwatching.